Case report: Early onset Marin-Amat syndrome after receiving ChAdOx1 nCoV-19 vaccination - Tsai, Ping-Feng; Chen, Ying-Jen (Frontiers in Medicine, 2022)
While vaccination against COVID-19 is still ongoing, some rare adverse events temporally related to vaccinations are needed to be reported, particularly ChAdOx1 nCoV-19. Here, a 77-year-old male presented to our outpatient department with persistent ptosis of his left eye for 1 month. He initially got vaccinated with ChAdOx1 nCoV-19 and developed symptoms of Bell’s palsy 3 days later. He received a course of 14-day prednisolone, and ptosis persisted. Marin-Amat syndrome was compatible with his symptoms of ptosis exacerbation when orbicularis oris exertion. Temporal correlation between ChAdOx1 nCoV-19 vaccination and Bell’s palsy without infectious or autoimmune diseases was delineated. Further studies are indicated to clarify the possible relationship between these two events.